Lymphocyte Nanomechanics in Response to Stent Implantation - Kapnisis, Konstantinos; Stylianou, Andreas; Kokkinidou, Despoina; Prokopi, Marianna; Anayiotos, Andreas (My University, 2021)
Changes in the arterial mechanical environment due to stent implantation are the main causes of the initiation of thrombosis and restenosis [1]. The mechanical properties of live cells can affect their physical interactions with the surrounding extracellular matrix, potentially influencing the process of mechanical signal transduction in living tissues. Previous studies have described the infiltration of inflammatory cells and immunocytes (T-lymphocytes) in restenotic tissue. This inflammatory response is characterized by the activation of circulating leukocytes that express adhesion molecules on the cell surface [2]. In this work we investigate stent-induced alterations in the nanostructure, cytoskeleton and mechanical properties of circulating lymphocytes in an effort to establish mechanical biomarkers to access stent-induced inflammation in the adjacent vascular tissue.
Keywords: Arterial mechanical environment; Stent implantation; Stent-induced alterations